2016
DOI: 10.1093/molbev/msw096
|View full text |Cite
|
Sign up to set email alerts
|

The Footprint of Polygenic Adaptation on Stress-ResponsiveCis-Regulatory Divergence in theArabidopsis Genus

Abstract: Adaptation of a complex trait often requires the accumulation of many modifications to finely tune its underpinning molecular components to novel environmental requirements. The investigation of cis-acting regulatory modifications can be used to pinpoint molecular systems partaking in such complex adaptations. Here, we identify cis-acting modifications with the help of an interspecific crossing scheme designed to distinguish modifications derived in each of the two sister species, Arabidopsis halleri and A. ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 93 publications
1
71
0
Order By: Relevance
“…Although some research studies have been designed to assess the response of NO or H 2 S individually to cadmium stress, the integrative roles of H 2 S and NO in plants under Cd stress are poorly understood. The adaptation of the plant to heavy metal stress is quite complex because of being a multigenic trait (He et al ). Plants have evolved extremely high and effective homeostatic systems to maintain the accumulation, translocation and detoxification of metals during the time of evolution and so it continues to be an important focus of several researchers (Adhikari et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some research studies have been designed to assess the response of NO or H 2 S individually to cadmium stress, the integrative roles of H 2 S and NO in plants under Cd stress are poorly understood. The adaptation of the plant to heavy metal stress is quite complex because of being a multigenic trait (He et al ). Plants have evolved extremely high and effective homeostatic systems to maintain the accumulation, translocation and detoxification of metals during the time of evolution and so it continues to be an important focus of several researchers (Adhikari et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Abiotic stresses including heavy metal pollution severely affect crop yield (Ma et al , O'Connor et al ). Cadmium is believed to be a highly toxic contaminant for all types of organisms, which passes in the soil mostly via anthropogenic applications such as manufacturing activities and usage of phosphate fertilisers and sewage sludge (Nagajyoti et al , He et al ). Earlier investigations have shown that cadmium is extremely poisonous to plants and it limits the production of plant biomass and even leads to plant death (Mobin and Khan , Rizwan et al ).…”
Section: Introductionmentioning
confidence: 99%
“…These compensatory stabilizing regulatory processes may, however, give rise to immediate expression novelty following genomic merger, where different cis and trans factors contributed by two divergent diploids become united in a common nucleus. Although these regulatory patterns have been explored in various plant systems (Springer & Stupar, ; Chaudhary et al ., ; Shi et al ., ; Bell et al ., ; Lemmon et al ., ; Xu et al ., ; Combes et al ., ; He et al ., ), we point out here that the classic ASE model fails to adequately parse the various forms of cis–trans interactions that are created by allopolyploidy. As such, advancing our understanding of the molecular and regulatory basis of phenotypic innovations that emerge following allopolyploidization requires this model to be extended.…”
mentioning
confidence: 84%
“…Allele-specific expression and eQTL mapping studies were first reported in yeast (Brem et al, 2002;Yvert et al, 2003;, mouse (Hubner et al, 2005;Wang et al, 2006) and human (Schadt et al, 2003;Morley et al, 2004;Monks et al, 2004;Bystrykh et al, 2005;Chesler et al, 2005;Cheung et al, 2005). In plants, most studies have focused on Arabidopsis thaliana (DeCook et al, 2005;Kiekens et al, 2006;Keurentjes et al, 2007;West et al, 2007;Cubillos et al, 2012bCubillos et al, , 2014He et al, 2016;Zan et al, 2016), maize (Stupar and Springer, 2006;Springer and Stupar, 2007a;Wang et al, 2018) and tree species (Kirst et al, 2004;in eucalyptus;Drost et al, 2010 in poplar;Combes et al, 2015 in coffee;Verta et al, 2016 in white spruce). These studies have successfully identified loci and polymorphisms involved in gene expression level regulation.…”
Section: Introductionmentioning
confidence: 99%